Seed Quality Determination of Different Teff [Eragrostis tef (Zucc.) Trotter] Seed Sources in Local Seed Business at Halaba Special Woreda and Meskan Woreda, South Ethiopia - SAMSON SEIFE,; R P S TOMER,; LEPIMA DESSALEGNE, (Seed Research, 2026)
The Meskan and Halaba Special Woredas are among Teff producing areas of South Nations Nationalities and Peoples Regional State. Despite the Woredas possesing a potential for Teff production, the productivity is low due to input and quality seed related problems. This study was designed to test seed quality of different sources and classes of Teff seed and to assess use of national seed quality standards by Local Seed Business in Halaba Special Woreda and Meskan Woreda in two seed producing cooperatives namely Napi Leka Nasi and Zerfeyan respectively. The physical purity and moisture content of all samples have met minimum standards of Teff Ethiopian National Seed Quality Standard. Only Certified-1 seed class met the minimum germination percentage of the National Standard while all the rest seed classes failed in germination test. Field emergence index was highly significant and positively correlated with speed of germination and vigor index-II and it was significantly and positively correlated with standard germination, vigor index-I, and seedling dry weight. The seed health quality of Teff seed samples was checked for the presence of fungal seed-borne pathogens using the agar plate method and seven major disease causing fungal genera were identified on Teff seed sources.